Synthesis and Characterization of Guar Gum Galactomannan Caproyl Ester - Mohamed, Sawsan Kamal; Ragab, Yousif Ali (Gezira Journal of Engineering and Applied Sciences, 2018)
A caproylated guar gum ester has been prepared from a homogeneous reaction of guar gum galactomannan by treatment in N,N-dimethylacetamide (DMAc)/ lithium chloride(LiCl) solvent system with caproyl (hexanoyl)  chloride (having a chain of 6 carbon atoms (C6). Caproylated guar gum ester has been synthesized with a degree of substitution DS=2.7. Elemental and FT-IR spectroscopy analysis confirmed occurrence of the substitution reaction. Study of thermal stability of purified guar gum galactomannan and its esters by differential scanning calorimetry (DSC) and thermal gravimetric analysis (TGA) showed that the caproylated guar gum galactomannan had improved thermal stability. The esters also showed enhanced solubility in some organic solvents and produced a water repellant fragile film. Synthesis of caproylated guar gum galactomannan ester may encourage the development of new guar gum based materials which may have additional useful functions as well as being biodegradable.